2007
DOI: 10.1124/jpet.106.114546
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Inhibits Topoisomerases, Depletes Mitochondrial DNA, and Triggers Steatosis in Mouse Liver

Abstract: Although tamoxifen can trigger steatohepatitis, the mechanism of steatosis is unclear. We hypothesized that this DNA-intercalating, cationic amphiphilic drug could accumulate within mitochondria to impair fatty acid oxidation, respiration, and mitochondrial DNA relaxation and synthesis. We studied the in vitro effects of tamoxifen on topoisomerases and mouse liver mitochondria and its in vivo hepatic effects in mice treated for 1 to 28 days with a daily dose of tamoxifen reproducing the plasma concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 34 publications
(70 reference statements)
5
116
1
Order By: Relevance
“…All of the deleterious effects induced by tamoxifen were highly exacerbated in the presence of estradiol [151]. Tamoxifen-induced inhibition of topoisomerases, mitochondrial DNA depletion and also the triggering of steatosis in mouse liver was also previously demonstrated [152]. The study demonstrated that tamoxifen is electrophoretically accumulated inside hepatic mitochondria, where it acutely impairs -oxidation and respiration.…”
Section: Mitochondrial Hepatic Toxicitymentioning
confidence: 69%
“…All of the deleterious effects induced by tamoxifen were highly exacerbated in the presence of estradiol [151]. Tamoxifen-induced inhibition of topoisomerases, mitochondrial DNA depletion and also the triggering of steatosis in mouse liver was also previously demonstrated [152]. The study demonstrated that tamoxifen is electrophoretically accumulated inside hepatic mitochondria, where it acutely impairs -oxidation and respiration.…”
Section: Mitochondrial Hepatic Toxicitymentioning
confidence: 69%
“…27 They showed 4-OHT was preferentially accumulated in mitochondria and inhibited both mtDNA synthesis and topoisomerase. It may be possible that 4-OHT treatment also triggers mtDNA deletions by inhibiting topoisomerase which causes insufficient relaxation to complete mtDNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…88 Higher intra-mitochondrial accrual of drugs like amiodarone, perhexiline or tamoxifen causes progressive reduction in mitochondrial respiration. 88,89 This leads to decreased ATP production in cells.…”
Section: Acquired Mitochondrial Disorders Of Livermentioning
confidence: 99%